Implementasi Etika Bisnis Islam dalam Pengelolaan dan Pelayanan Unit Bisnis Wahdah Islamiyah - Andi Wawan Mulyawan; Koesmawan Koesmawan (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to: (1) analyze the implementation of the concept of Islamic business ethics in the service of Wahdah Islamiyah business units; and (2) analyzing the use of the concept of Islamic business ethics in the service of Wahdah Islamiyah business units. This research is a field research (field research) using qualitative methods that are carried out in a descriptive analysis. The results of this study indicate that: first, all informants (100%) answered that the principles/ethics of monotheism had been applied/practiced, the majority of informants (61.5%) answered that the principles or ethics of justice had been applied/practiced, as many as 42.3% of informants chose very appropriate and 42.3% of informants chose appropriate regarding the application/practice of the principles/ethics of trustworthiness, and as many as 19 people or 73.1% of informants chose very appropriate regarding the application/practice of the principles/ethics of virtue and honesty; second, the Islamic business principles/ethics that have been implemented provide great benefits and uses for the management and service of business units within Wahdah Islamiyah, where the implementation of the principles/ethics of monotheism is believed to bring blessings, the implementation of the principles/ethics of justice is believed to create a work environment that is fair, inclusive, dignified, and in accordance with Islamic law, the implementation of the principles/ethics of trustworthiness is believed to be able to increase the trust of customers and other parties, and the implementation of the principles/ethics of virtue/honesty is believed to be able to improve and provide excellent service to all parties.